Education for citizenship - Robertson, T.M. (My University, 1897)
Introduction: With each succeeding re-occurrence of a Presidential campaign arises the question of qualification for voters. Especially since the last campaign, has the general movement toward securing a more intelligent ballot, assumed a definite shape; as seen in the wide-spread organization of the Good Citizenship Leagues. In our free democratic form of government, which has shown itself in advance of all other forms; where each individual vote counts, or should count, equal; any advancement or improvement in the methods of the governmental policy, must of necessity be brought about by a process of education of the individual voters. The question arises, how is this object to be secured? One method is; to begin with the public schools. The public school is established, and maintained at public expense, with the purpose, and expectation in view, that the student will, in time, repay the government, in part, for the expense of the education, by making a better class of citizens.
Citation: Robertson, T.M. Education for citizenship. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Education; Citizenship; Informed electorate; Voting; Theses; Manuscripts (documents)